Inap desa sebagai satu agen pembangunan sosioekonomi komuniti: Menelusuri perspektif pelajar-pelajar Pengurusan Pelancongan UUM - Ahmad, Mohamad Zaki; Ibrahim, Johan Afendi; Zakaria, Norria (2011)
Tourism industry has proven to be one of the national major income contributors over the last decade. Efforts and planning considerations have been undertaking mainly by various government agencies to further develop this industry, particularly to enhance its contribution towards socioeconomic development of Malaysian society."Inap desa" or popularly known as homestay is one of the rural tourism products in Malaysia and has emerged as a program that often gets the attention of government and its related agencies in recent years.As the number of participants, as well as number of rooms of offered is on the rise, the country's homestay sector that generated revenues close to RM10.9 million in 2009 has great potentials to become an agent for socioeconomic development, particularly for rural communities. Based on reports of coursework by students of Tourism Management Universiti Utara Malaysia (UUM) on the development of homestay for several states in Peninsular Malaysia, aspects such as definition and concept of homestay, growth and development of homestay tourism, SWOT analysis and impacts of homestay development will be discussed and further clarified.